Health related quality of life in children and adolescents and associated factors - Gaspar, Tania (2014)
The main objective of this study was to propose a model, which includes personal and social factors associated to health-related quality of Life (HRQoL) in children and in adolescents. A sample of 3195 children and adolescents was randomly selected from 5th and 7th graders, in Portuguese public schools. The Portuguese versions of KIDSCREEN-52, Harter’s SPPS, LOT-R, SSSS and HBSC (selected items) were used to evaluate personal and social factors and health behaviors. Various structural equation models were developed in association with gender, age, socioeconomic status (SES) and using the global sample. The studied models presented good adjustment indexes, which suggest a good fit for the hypothesized model. The psychosocial variables have a strong impact in the HRQoL. Consequently, health promotion programs for children and adolescents should include the psychosocial approach. Based on our results, we discuss and propose strategies to develop HRQoL in children and adolescents, in schools and in families.